2013
DOI: 10.1007/s00586-013-2686-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty for osteoporotic vertebral compression fracture with intravertebral cleft associated with delayed neurologic deficit

Abstract: Introduction The number of cases of osteoporotic vertebral compression fracture (OVCF) with intravertebral cleft (IVC) with delayed neurologic deficit (DND) is increasing as the population ages. However, the cause of DND is poorly understood, and no definitive treatment of the disease has been established. The purpose of this study was to clarify the radiographic parameters contributing to the occurrence of DND, and to evaluate the efficacy and safety of percutaneous vertebroplasty for this pathology. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Owing to the progression of kyphosis with vertebral collapse and intravertebral instability at the cleft site, patients with advanced-stage Kummell's disease are more susceptible to neurological deficits [19]. Minimally invasive procedures, such as percutaneous vertebroplasty (PVP) or percutaneous kyphoplasty (PKP), have been widely applied once conservative treatment fails for OVCFs with IVC [10,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the progression of kyphosis with vertebral collapse and intravertebral instability at the cleft site, patients with advanced-stage Kummell's disease are more susceptible to neurological deficits [19]. Minimally invasive procedures, such as percutaneous vertebroplasty (PVP) or percutaneous kyphoplasty (PKP), have been widely applied once conservative treatment fails for OVCFs with IVC [10,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive procedures, such as percutaneous vertebroplasty (PVP) or percutaneous kyphoplasty (PKP), have been widely applied once conservative treatment fails for OVCFs with IVC [10,[20][21][22][23]. Although a few studies have confirmed that vertebroplasty could be an alternative intervention for the effective and safe treatment of OVCFs with IVC complicated by neurological deficits, patients with low intravertebral stability and severe spinal cord injuries should be considered candidates for reconstructive surgery [19]. Currently, several open surgery options, mainly consisting of posterior fixation combined with vertebroplasty (PFVP) or vertebral column resection (PVCR) for IVC complicated by neurological deficits, have been reported in the literature [20,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, vertebroplasty or kyphoplasty is less effective for spinal stability or neurological recovery, and Nakamae et al . also reported that it is ineffective in cases of high‐grade spinal canal compromise and an absence of remarkable dynamic instability. Furthermore, increasing attention on health and developments in medicine have created rapid growth of the aging population.…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Nakamae et al [22], which also appears in the July issue deals with osteoporotic vertebral compression fractures (OVCF) with an intervertebral cleft (IVC) and delayed neurologic deficit (DND). The aim of this study was to clarify the mechanisms of delayed neurologic deficit and evaluate the efficacy of percutaneous vertebroplasty in OVCF with IVC associated with DND.…”
Section: Vertebroplastymentioning
confidence: 99%